2012
DOI: 10.1111/pbr.12003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genotypic variation for normalized difference vegetation index and its relationship with grain yield in winter wheat under terminal heat stress

Abstract: Normalized difference vegetation index (NDVI), which is a measure of leaf greenness (chlorophyll content), is considered to be correlated with crop productivity. This study was conducted to examine genotypic variations for NDVI at different growth stages and its relationship to yield in winter wheat under terminal heat stress. Thirty winter wheat genotypes were evaluated at two locations in 2009–2010 and 2010–2011 in Uzbekistan. The NDVI was recorded at booting, heading, milk and dough stages. The wheat genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
(43 reference statements)
3
20
0
Order By: Relevance
“…The predictive value of NDVI for grain yield and other traits can be improved via some modifications in NDVI calculations, such as degree of NDVI reduction after anthesis (Hazratkulova et al, 2012), NDVI ratio before and after anthesis, and cumulative NDVI after anthesis (Li et al, 2011). There is value in relating spectral reflectance parameters to canopy and air temperature to reduce the effect of weather and differences related to maturity variation between genotypes (Kimball et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value of NDVI for grain yield and other traits can be improved via some modifications in NDVI calculations, such as degree of NDVI reduction after anthesis (Hazratkulova et al, 2012), NDVI ratio before and after anthesis, and cumulative NDVI after anthesis (Li et al, 2011). There is value in relating spectral reflectance parameters to canopy and air temperature to reduce the effect of weather and differences related to maturity variation between genotypes (Kimball et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis aimed to provide baseline information on the relationship between key environmental parameters and the reflectance of the bands/VIs. The bands and VIs were chosen within the ones currently used in other crops to characterize heat stress [31,[73][74][75][76]. The examination was carried out on the entire trial area using the Sentinel-2 time series available over the two growing seasons, 2016-2017 and 2017-2018 (31 images).…”
Section: Analysis Of Remote Sensing Datamentioning
confidence: 99%
“…However, there are also contradictory reports regarding the relationship between NDVI measured at different growth stages and yield (Hazratkulova et al 2012). An association between NDVI and yield during the grain-filling stage in wheat has been reported by some researchers (Hazratkulova et al 2012;Freeman et al 2003), while other studies showed associations of yield and NDVI at the booting, heading and grain-filling stages (Babar et al 2006b). Identification of common chromosome regions shared by NDVI and biomass and yield should be helpful in understanding the genetic basis of the relationship between these traits, and should allow breeders to utilize the trait as an indirect selection criterion for grain yield improvement.…”
Section: Introductionmentioning
confidence: 99%